The Relationship between Emotional Intelligence and Internet Addiction among Junior High School Adolescents in Tangerang and Jakarta - Graciela, Evelyn; Tiatri, Sri (Peneliti.net, 2023)
In the 2020s, the internet has increasingly facilitated access, leading to a rise in its usage frequency. Adolescents often struggle to control their internet usage. Emotional intelligence is one factor that can help regulate internet use. When adolescents reach the age of 18-21, it is found that those already addicted find it difficult to change their behavior. Therefore, efforts and understanding are needed regarding adolescents in their earlier years, specifically, those aged 12-15. This research aims to examine the relationship between emotional intelligence and internet addiction. The study adopts a quantitative correlational method, involving 150 students aged 12-15 from X Junior High School in Tangerang and X Junior High School in Jakarta. Measurements include tools for assessing emotional intelligence and internet addiction. The results indicate a negative correlation between emotional intelligence and internet addiction, meaning that higher emotional intelligence is associated with lower internet addiction. Based on the findings, to prevent internet addiction, emotional intelligence needs to be enhanced, although the results also show an inverse relationship.